Affectors on The Financial Distress of Businesses Listed on The Indonesian Stock Exchange: Hotel, Restaurant, And Tourism - Sjamsudin, Adella Vanessa; Asiah, Antung Noor; Munawaroh, RR Siti; Syahdan, Saifhul Anuar; Nastiti, Rizky; Dermawan, Budi (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
The purpose of this research is to ascertain how operating capacity, liquidity, profitability, and leverage affect financial hardship in lodging, dining, and tourism businesses that are listed on the Indonesia Stock Exchange. With 35 hotel, restaurant, and tourism enterprises listed on the Indonesia Stock Exchange, this study employs quantitative methodologies. Additionally, 12 companies were selected as samples through the use of purposive sampling. In this work, logistic regression analysis, hypothesis testing, and descriptive statistics were employed as data analytic approaches. The findings demonstrate that the profitability ratio significantly and negatively impacts financial strain. This finding suggests that a company's financial performance improves with increased profitability, putting it in a better position to avoid financial trouble. Additionally, there is a noteworthy and positive correlation between the liquidity ratio and financial difficulty. It demonstrates that a company's likelihood of experiencing financial problems increases with its liquidity. Conversely, there is a negligible and adverse impact of the leverage ratio on financial distress. This finding suggests that a company's amount of leverage has an effect on the financial difficulties it experiences. Furthermore, financial distress is positively and significantly impacted by the operational capacity ratio. This finding demonstrates that the likelihood of experiencing financial trouble increases with TATO